Restoring Economic Growth in Argentina - Cline, William R. (World Bank, Washington, DC, 2014)
The author reviews the debate on the causes of Argentinas economic collapse in late 2001 and 2002 and examines the measures needed to help restore sustainable growth. Some analysts stress fiscal imbalances, others overvaluation of the peso under the convertibility plan, and others external shocks. Cline judges that all three contributed substantially, but that it was their inflammatory interaction with domestic political unraveling that forced the bad-equilibrium outcome. He reviews the nascent recovery since the second half of 2002 and the important success of avoiding hyperinflation. Looking forward, the authors analysis underscores the importance of strengthening fiscal performance, in part by increasing relatively low collections of value added taxes. He stresses the need for reform of the system of revenue sharing with the provinces; the importance of strengthening the banking system, which was severely weakened by asymmetric conversion of assets and liabilities from dollars to pesos; and the need to arrive at equitable restructuring of utility tariffs to reestablish confidence of foreign direct investors in the rules of the game. Restructuring government debt is also central to restoring growth. A simple model indicates that a relatively ambitious target for the primary fiscal surplus and a restricted set of senior-status debt will be needed to limit the haircut on junior debt to amounts compatible with longer-term creditor perceptions of fairness. The author also considers the new dynamics of bargaining with the International Monetary Fund (IMF). He judges that although conditionality is arguably appropriately less stringent as only rollover is involved, and despite the large outstanding debt to the IMF, there are limits to how lenient the Fund can and should be in key areas with potential for setting international precedents.